Analyzing a fleet solution using scenarios - Martins, A.; Nunes, Ana Catarina; Carvalho, B. (INTSYS 2019, 2019)
Transportation is one of the most important logistics activities, accounting for a significant part of the logistics costs and with high level of impact in terms of the service level provided to the customer. To counteract the upward trend in costs, it is fundamental to identify a transport strategy that can reduce costs and, at the same time, does not adversely affect the service levels agreed with customers. The main objective of this research is to propose a methodology for companies to identify, from a set of scenarios proposed and through a comparative analysis of scenarios, a new fleet solution, allowing the Company under study to reduce its transport costs without harming the current service level agreements with its cus-tomers. This research is grounded on a case study methodology. The case study used is of a small Portuguese company that produces, imports and distributes a wide range of products. The distribution is conducted based on both its own fleet and subcontracted transportation. The comparative analysis of scenarios allowed identifying the current transportation solution as the most advantageous one for the company. A roadmap to address fleet solution is provided.